Feasible speeds for two optimal periodic walking gaits of a planar biped robot. Issue 2 (4th February 2022) - Hobon, Mathieu; De-León-Gómez, Víctor; Abba, Gabriel; Aoustin, Yannick; Chevallereau, Christine
Abstract: The purpose is to define the range of feasible speeds for two walking motions for a particular planar biped robot, which differ in the definition of their finite-time double support phases. For each speed, these two walking motions are numerically obtained by using a parametric optimization algorithm, regarding a sthenic criterion. Results allow us to define the range of allowable speeds for each walking. One result is that the first gait is less consuming in energy for moderate to fast velocity with respect to the second one, while the second gait is more efficient for low walking velocity.